Influence of Sociodrama on The Emotional Intelligence of Preschool Children - Ulya, Himatul; Putri, Erika Setyanti Kusuma (ANIMA Indonesian Psychological Journal, 2010)
The influence of socio-drama on preschool children in increasing their emotional intelligence was analysed, including the effectiveness of the game. Subjects were 5-6 years old children attending preschool class at ‘Aisyiyah Bustanul Athfal kindergarten (N = 22). After attending six sessions of socio drama, the children’s emotional intelligence was measured by test of emotional intelligence with Goleman’s indicators. The children were tested, pre and post treatment, and t-test was applied. The results showed the value of t =7.160 with p = .000 (p < .01). The result shows that socio drama can significantly contribute) to children’s emotional intelligence. It means that socio-drama is effective in enhancing preschool children’s emotional intelligence. Telah dianalisis pengaruh sosiodrama terhadap kecerdasan emosi anak usia prasekolah untuk meningkatkan kecerdasan emosi mereka, termasuk efektivitas dari permainan tersebut. Para subjek adalah anak usia 5-6 tahun yang bersekolah di Taman Kanak-kanak ‘Aisyiyah Bustanul Athfal Pringwulung (N = 22). Subjek mengikuti enam sesi sosiodrama. Setelah enam sesi, kecerdasan emosi anak-anak tersebut diukur menggunakan tes kecerdasan emosi dengan indikator kecerdasan emosi dari konsep Goleman. Tes tersebut diberikan melalui pre-test dan post-test. Analisis statistik yang digunakan untuk mengetahui pengaruh sosiodrama terhadap kecerdasan emosi anak usia prasekolah adalah uji-t. Hasil-hasil menunjukkan nilai t sebesar 7.160 dengan nilai p = .000 (p < .01). Hasil tersebut menyatakan bahwa sosiodrama memberikan kontribusi yang berarti bagi kecerdasan emosi anak. Hal ini berarti sosiodrama efektif dalam meningkatkan kecerdasan emosi anak usia prasekolah.